(untitled) - Pacey, Arnold (England, 1983)
Contents: The Culture of Technology examines carefully our often conflicting attitudes toward nuclear weapons, biological technologies, pollution, third world develoment, automation, social medicine, and the industrial decline of Britain.
Keywords: Công nghệ,Technology; Khía cạnh xã hội,Social aspects